Royalism, religion, and revolution: the gentry of North-East Wales, 1640-1688 - Ward, S (2016)
This thesis focuses specifically on the gentry of North-East Wales. It addresses the question of the uniqueness of the region’s gentry in relation to societal organisation, authority, identity, religion, and political culture. The thesis examines the impact of the events of 1640 to 1688 on the conservative culture of the region. It assesses the extent to which the seventeenth-century crises changed that culture. Additionally, it discusses the distinctiveness of the Welsh response to those events. This thesis offers new arguments, or breaks new ground, in relation to three principal areas of historiography: the questions of Welsh identity, religion, and political culture. Within Welsh historiography this thesis argues for a continuation of Welsh identity and ideals. It uncovers a royalist, loyalist, and Anglican culture that operated using ancient ideals of territorial power and patronage to achieve its ends. In doing so it overturns a lingering idea that the Welsh gentry were anglicised and alienated from the populace. The thesis also interacts with English debates on the same themes. In exploring the unique aspects of the culture of North-East Wales, the assertion of an anglicised monoculture across England and Wales can be disproven. This allows for a more complex picture of British identity, religion, and politics to emerge. This thesis musters correspondence, material objects, diaries, notebooks, accounts, official documents, and architectural features to aid in its analysis. This breadth of evidence allows for a broad analysis of regional patterns while allowing for depth when required. The first three chapters of the thesis examine the North-East Welsh gentry in relation to the themes of Welsh society and identity; religion; and finally political culture. The final chapter comprises three case studies that explore aspects of the aforementioned themes in further depth.